Patient Experience for Hispanic Older Adults Varies by Language Preference. Issue 12 (18th December 2022) - Weech-Maldonado, Robert; Haviland, Amelia M.; Hambarsoomian, Katrin; Martino, Steven C.; Dembosky, Jacob W.; Tamayo, Loida; Gaillot, Sarah; Elliott, Marc N.
Abstract : Background: Hispanic people with Medicare report worse patient experiences than non-Hispanic White counterparts. However, little research examines how these disparities may vary by language preference (English/Spanish). Objectives: Using Medicare Consumer Assessment of Healthcare Providers and Systems (CAHPS) survey data, assess whether 2014–2018 disparities in patient experiences for Hispanic people with Medicare vary by language preference. Research Design: We fit a series of linear, case-mix adjusted models predicting Medicare CAHPS measures by race/ethnicity/language preference (Hispanic Spanish-respondents; Hispanic Spanish-preferring English-respondents; Hispanic English-preferring respondents; and non-Hispanic White English-respondents). Subjects: A total of 1, 006, 543 Hispanic and non-Hispanic White respondents to the Medicare 2014–2018 CAHPS surveys. Results: There were disparities for all Hispanic groups relative to non-Hispanic White English-respondents. Hispanic Spanish-preferring English-respondents reported worse experience than Hispanic Spanish-respondents for getting care quickly (−8 points), getting needed care (−5 points), doctor communication (−2 points), and customer service (−1 point), but better experiences for flu immunization (+2 points). Similarly, Hispanic Spanish-preferring English-respondents reported worse experience than Hispanic English-preferring respondents for getting care quickly (−4 points) and getting needed care (−2 points). Hispanic English-preferring respondents reported worse experience than Hispanic Spanish-respondents for getting care quickly (−4 points), getting needed care (−3 points), doctor communication and customer service (−2 points each), but better experience for flu immunization (+2 points). Conclusions: Regardless of language preference, Hispanic people with Medicare experience disparities in patient care relative to non-Hispanic White English-preferring counterparts. Hispanic Spanish-preferring English-respondents report the worse experiences, followed by Hispanic English-preferring respondents. Hispanic Spanish-respondents experienced the least disparities of the three Hispanic language subgroups.